Wake characterisation and simulation for ground vehicles - Soares, Renan Francisco (Cranfield University, 2020)
This project aims to develop a generic, adaptable device able to emulate the distinct aerodynamic wake characteristics corresponding to different closed-wheel automotive vehicle categories, avoiding the use of a full-body vehicle model(s). The intention is to reduce complexity in both wind tunnel experimental testing and computational simulation, enhancing the capability of experimental facilities to study interference effects between vehicles in close proximity (e.g. platoon formation, drafting) and allowing faster build, meshing and computation time for CFD studies. The overall approach uses both computational and experimental investigationson generic automotive configurations (e.g. DrivAer models), particularly in relation to wake development and detailed flow structures. CFD simulations are mainly used for preliminary flow analysis and aerodynamic design, while the wind tunnel established the experimental, benchmark datasets. The three standard DrivAer vehicle configurations were adopted for studies relating to passenger cars, while the proposed 4th configuration (‘high-performance’) was developed and proposed as a benchmark model for race car aerodynamics. Two extensive, experimental wake datasets on the four DrivAer configurations have been created, the first using a pressure-based technique (total pressure rake), and the second applying an image-based method (Stereoscopic Particle Image Velocimetry). Additional experimental analyses support each wake dataset, such as (i) investigation of the effects of experimental conditions, (ii) Reynolds number characteristics and (iii) statistical analysis .These automotive wake benchmarks were used as the basis for the development of a conceptual wake generator, which is intended to be adaptable and able to ii generate representative wakes equivalent to automotive bodies. The development and key aerodynamic characteristics of this device are outlined, and each configuration experimentally validated using wind tunnel data. The complex wake structures associated with each of the four vehicle configurations are categorised, and the resulting wake emulator is seen to be capable of reproducing the key features within the wake development region of interest (i.e.0.666<𝑥/𝑊<1.33, where 𝑥/𝑊 is the distance behind the vehicle normalised by the DrivAer model width, 𝑊). This thesis is concluded with the proposal of a wake generator device as a new tool to support further development on automotive aerodynamics.
Keywords: Automotive aerodynamics; bluff-body wake generator; PIV wake database; total pressure wake database; CFD design